All that glitters - Fox, Ilana (Orion Books, 2012)
Ella Aldridge seems to have it all. Married to Danny Riding, one of the Premiership's leading goal-scorers, she lives the dream - the mansion, the car, the freebie designer clothes. But Ella and Danny have a secret. Their marriage is not what is seems. Between them, it takes a lot of hard work to fool the press and the nation that they really are Love's Young Dream, when deep down Danny's desires lie elsewhere. With Ella's star in the ascendant, the world is at her feet - a TV show, a fashion column. But then she meets Johnny Cooper, the bad boy of British television. He's ruthlessly charming and sexy, and he can see through Ella's sham of a marriage in a heartbeat. Drawn into a risky, high-octane affair, Ella suddenly realises how much she has to lose and how quickly it can be taken from her ...